Plastics additives : an industrial guide - Flick, Ernest W. (William Andrew, 2002)
Contains plastics additives' formulations based on information received from industrial companies and other organizations.
Includes index.
Keywords: Plastics -- Additives.; elektronické knihy; electronic books